Use of PRP for treatment of tibia fracture with delayed consolidation: case report - Maslennikov, S. O.; Kozhemyaka, M. O.; Масленніков, Сергій Олегович; Кожем'яка, Максим Олександрович (My University, 2022)
Delayed consolidation of fractures is one of the most frequent complications in orthopedic practice. With the development of new methods of regenerative medicine, including Platelet-Rich Plasma (PRP), new possibilities for conservative treatment of this problem have emerged. This article presents a clinical case of conservative treatment of delayed consolidation of a tibial fracture using local PRP injections. In the fracture space, PRP releases various inducers of tissue growth and acting on receptors indirectly causing a chemotactic effect, mobilizes the body’s own resources and create conditions for angiogenesis and trophism of injured segment. All PRP factors affect the vascular and cellular components, without which bone restoration is not possible. In the patient with delayed consolidation after PRP treatment, progress in clinical and radiological dynamics with complete healing within 1 year is noted. A positive clinical result provides a basis for further study and implementation in practice.
Keywords: tibial fractures; hypoporosis; platelet-rich plasma; osteosynthesis